Function of the Chloroplast Hydrogenase in the Microalga Chlamydomonas: The Role of Hydrogenase and State Transitions during Photosynthetic Activation in Anaerobiosis - Ghysels, Bart (Public Library of Science, 2013)
Like a majority of photosynthetic microorganisms, the green unicellular alga Chlamydomonas reinhardtii may encounter O(2) deprived conditions on a regular basis. In response to anaerobiosis or in a respiration defective context, the photosynthetic electron transport chain of Chlamydomonas is remodeled by a state transition process to a conformation that favours the photoproduction of ATP at the expense of reductant synthesis. In some unicellular green algae including Chlamydomonas, anoxia also triggers the induction of a chloroplast-located, oxygen sensitive hydrogenase, which accepts electrons from reduced ferredoxin to convert protons into molecular hydrogen. Although microalgal hydrogen evolution has received much interest for its biotechnological potential, its physiological role remains unclear. By using specific Chlamydomonas mutants, we demonstrate that the state transition ability and the hydrogenase function are both critical for induction of photosynthesis in anoxia. These two processes are thus important for survival of the cells when they are transiently placed in an anaerobic environment.